Egalités démocratiques. Pour une histoire conceptuelle de l'émancipation à partir de Jacques Rancière - Le Borgne de Boisriou, Valentine (2014)
Equality crosses the work of Jacques Rancière: primarily the assumption of equality, but also, and especially, its consequences: those of the radical power introduced by this possibility always open of breaking the oppression’s logics. Furthermore, the thought of Jacques Rancière is a thinking movement, built around dinstinctions and proximities with some authors, sometimes contemporary, but also voices and figures from a past in which Rancière research track of equality constitutive of the community (Jacotot). This article then proposes to explore, from the notion of equality, the affinities and ruptures built by Jacques Rancière, giving place to a definition of the equality for Rancière. So we'll see how Rancière opposes Habermas, depending on whether one considers that equality is proposed for consensus or otherwise, from a dissent; Rawls, when we consider the effects of the difference between the ability of anyone to say the wrong, and the fair distribution of the maximum possible equality. With the confrontation of Rancière with Bourdieu, we will see that the same concern for the word produces different effects, depending on whether one considers the domination mutes or incites a speech disruptive. Finally, with Balibar and Abensour, we'll see how emerges the definition of an infinite democratic equality.